Projeto arquitetônico de um hospital veterinário para a cidade de Belém - Gutierrez, Michelle Lavôr (2019)
This Final Graduation Work contemplates the development of an architectural project of a Veterinary Hospital for small and medium-sized animals, aiming at the planning of the appropriate environment for the animals and owners that will be attended there, following all the requirements and regulations applicable to a hospital architecture, with a proposed location in the city of Belém, Pará. The study and proposal value the specialized care to the pet population and their owners, as well as research spaces, inserted in a large structured space with comfort and a high standard, designed for also contribute to the aesthetics and enhancement of the urban environment.